Polish Legal Bibliography of Environmental Law - Walas, Martyna Joanna (Polish Yearbook of Environmental Law, 2018)
Report includes Polish Legal Bibliography of Environmental Law for period: 1st August 2016 – 31st October 2017. It was edited on the basis of Polish Legal Bibliography in Państwo i Prawo and Bibliography of Polish Academy of Sciences.